PERAN E-SATISFACTION DALAM MEMEDIASI HUBUNGAN E-SERVICE QUALITY TERHADAP E-LOYALTY - Shamia, Shamia; Piartrini, Putu Saroyini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p06, 2023)
The development of technology and the internet in Indonesia is increasing. This has an impact on changes in people's online shopping activities, especially through e-commerce applications. The use of e-commerce in Indonesia is also increasing from year to year. This condition also makes so many e-commerce pop up in Indonesia so that every company needs to improve and maintain consumer loyalty in the midst of the existing competition. This study uses expectation confirmation theory and prospect theory as the basis for thinking about the relationship between e-service quality, e-satisfaction and e-loyalty. This study aims to explain the role of e-satisfaction in mediating the relationship between e-service quality and e-loyalty. Based on the results of a survey of 135 consumers on the Tokopedia application in Denpasar City, the results of the Baron and Kenny Steps regression analysis and the Sobel test show that all hypotheses are accepted. E-Service Quality has a positive and significant effect on e-loyalty. E-Service Quality has a positive and significant effect on e-satisfaction. E-satisfaction has a positive and significant effect on e-loyalty. E-satisfaction is able to partially mediate the relationship between e-service quality and e-loyalty